PENGARUH PEMBERIAN KOMPRES HANGAT PADA LEHER UNTUK MENGURANGI NYERI DI KEPALA PADA PASIEN HIPERTENSI - Arfah May Syara; Tiurma Siringoringo; Afeus Halawa; Kristina Sitorus (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2021)
Hypertension or high blood pressure is an abnormal increase in blood pressure in the arteries or an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg in two measurements with an interval of five minutes in a fairly calm/resting state. Common signs and symptoms that arise from hypertension are sore neck (neck pain). Neck pain due to hypertension makes the comfort needs of hypertensive patients not met. One of the non-pharmacological measures to reduce or overcome neck pain is a warm compress. A warm compress is giving a feeling of warmth / heat in a certain area. neck pain scale in hypertensive patients before warm compress therapy, said moderate pain 4 respondents (28.6%), severe pain 10 respondents (71.4%) with a standard deviation of 0.469. The pain scale of hypertensive patients after warm compress therapy was said to be moderate for 12 respondents (85.7%), the weight of 2 respondents (14.3%) with a standard deviation of 0.426. Hypertensive patients who experienced severe neck pain decreased, before being given treatment as many as 10 people, after being given treatment as many as 2 people. The application of warm compresses to hypertensive patients continues to be carried out for non-pharmacological therapy that can be carried out by the community at home.